The world : a brief introduction - Haass, Richard (New York : Penguin Press, 2020)
"This book is designed to provide readers with the background and building blocks they need in order to answer for themselves the critical questions about what is taking place around the world and why. It explains what makes each region of the world tick, the many challenges globalization presents, and the most influential countries, events, and ideas. Its aim is to help readers become more informed, discerning citizens, better able to arrive at sound, independent judgments and less vulnerable to being misled"--
From the Thirty Years' War to the outbreak of World War I (1618-1914) -- From World War I through World War II (1914-1945) -- The Cold War (1945-1989) -- The post-Cold War era (1989-present) -- Europe -- East Asia and the Pacific -- South Asia -- The Middle East -- Africa -- The Americas -- Globalization -- Terrorism and counterterrorism -- Nuclear proliferation -- Climate change -- Migration -- The Internet, cyberspace, and cybersecurity -- Global health -- Trade and investment -- Currency and monetary policy -- Development -- Sovereignty, self-determination, and balance of power -- Alliances and coalitions -- International society -- War between countries -- Internal instability and war within countries -- The liberal world order.
Includes bibliographical references and index : pages [315]-370.
(3ebQQGJ OQGSjI dWdGH GdLGeYI (B2024.s
Keywords: International relations -- History; World politics; History, Modern